Growth Modification of Developing Class II Division 1 Malocclusion Using Myofunctional Appliances - Ananto Ali Alhasyimi; Iman Syahfik (Case Reports in Dentistry)
Background and Overview. Interceptive orthodontics is a phase of orthodontics that identifies and corrects potential malocclusions in the growing dentofacial complex. At this point, myofunctional appliances are a necessary component. A 9-year-old girl appeared with a Class II division 1, a 6 mm overjet, a 6 mm overbite, a V-shaped maxillary arch, as well as lip hypertonicity, and an overdeveloped maxilla. Myobrace® combines the dental alignment abilities of rigid and soft appliances. Its structure replicates a fixed appliance: the soft outer part acts as the orthodontic wire, whereas the inner hard part engages the teeth individually. After 12 months of treatment, facial photos and a cephalogram were taken, both of which demonstrated an enhancement to the patient’s facial profile. Conclusions and Practical Implications. This case demonstrates that Myobrace® may be a simple and good choice to treat skeletal malocclusion with oral habit because of its greater compliance and favorable results. In certain instances, an early approach, taking into account patient preferences and compliance, is practical and should be considered in future treatment planning and research.